2017
DOI: 10.1002/asjc.1500
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis for Discrete Event Systems Modeled By Bounded Petri Nets

Abstract: Fault diagnosis is an important problem in the manufacturing industry. It has been extensively studied in the past few decades both in time‐driven systems and discrete event systems. This paper presents a Petri net diagnoser for online fault diagnosis of discrete event systems modeled by bounded labeled Petri nets. First, we present the concept and some properties of an extended basis reachability graph. Next, based on such a graph, we construct a Petri net diagnoser that is used to determine if a fault has oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
(57 reference statements)
0
6
0
1
Order By: Relevance
“…A diagnoser model including four places was proposed to reduce the number of tokens in its places. In , the authors presented a diagnosis approach for LPNs with partially observed transitions whose unobservable subnet was acyclic. The faults were not necessarily modeled by unobservable transitions but might also have been modeled by undistinguishable observable transitions.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnoser model including four places was proposed to reduce the number of tokens in its places. In , the authors presented a diagnosis approach for LPNs with partially observed transitions whose unobservable subnet was acyclic. The faults were not necessarily modeled by unobservable transitions but might also have been modeled by undistinguishable observable transitions.…”
Section: Related Workmentioning
confidence: 99%
“…However, the BRG computation is exponential with respect to the number of nodes. In order to reduce the complexity of their method, the authors in constructed a PN diagnoser based on an extended basis reachability graph that was of polynomial complexity in the number of nodes for a bounded LPN. For the fault diagnosis of a DES modeled by logic PN with partially observed transitions, Lefebvre proposed a method that provided diagnosis decisions via the analysis of observation sequences decomposed into elementary observation sequences.…”
Section: Related Workmentioning
confidence: 99%
“…Dans [CABASINO et al 2013], il est montré que si le RdP étiqueté est borné, la construction hors-ligne d'un automate appelé graphe d'accessibilité de base (BRG) est possible, utilisé pour un diagnostic en-ligne. Un BRG étendu (EBRG) a été construit dans [RAN et al 2017] qui est un automate basé sur des marquages de base calculés en supposant que toutes les fautes du système sont observables. Géneralement, le EBRG admet beaucoup moins de noeuds que le graphe d'accessibilité, mais ce nombre reste important.…”
Section: Introductionunclassified
“…In (Ramirez et al, 2012), the difference of the marking of the actual behavior model and the estimated marking, called residue, provided enough information for the immediate isolation of faults. In (Cabasino et al, 2013;Ran et al, 2017), a diagnosis approach of partially observed LPN was based on the notion of basis markings which was a reduced set of actual markings coherent to an observed sequence. The faults were modeled by unobservable transitions and might also been modeled by undistinguishable observable transitions.…”
Section: Introductionmentioning
confidence: 99%
“…If the LPN was bounded, the diagnosis approach was based on the Basis Reachability Graph (BRG) which can be computed off-line. An Extended BRG (EBRG) was constructed in (Ran et al, 2017) which is a basis marking computed by assuming that all the system faults are observable. The EBRG has significantly fewer states than the reachability graph in most cases, but it still exponential with respect to the number of nodes.…”
Section: Introductionmentioning
confidence: 99%